(untitled) (Research, Society and Development, 2022)
Objective: After signing the final document of COP 26, many countries will look for initiatives related to Clean Development Mechanism Projects, the CDM’s, giving priority to those related to carbon capture and mitigation of atmospheric emissions. However, the approval of these projects is not easy and few are approved in Brazil. The study aims to present a collection of projects approved in Brazil between 2017-2021. Methodology: Exploratory Qualitative Bibliographic Review. Result and Discussion: Projects proposed for the destination of CDM’s are not common in the search for compensation or environmental protection, it needs to be innovative, monitored and its performance must be measured and evidenced. In Brazil and Brazil, there are few projects cited in the literature review and many are associated with protecting forests – capturing CO2 and replacing energy from fuels with renewable energy. Conclusion: Some successful projects are being developed in Brazil, but with COP 26, Brazil, as the holder of sensitive ecosystems of extreme importance for the global environmental balance, if well explored, will attract interest in investment in the coming decades not only in maintaining the balance of these environments as well as the benefits for the whole society that lives and subsists from these natural resources. In this way, CDM’s can be better developed in less developed regions of the country, but with great environmental potential. It is suggested to increase investments and foster research institutions together with private companies that develop projects.